DESIGN AND TESTING OF A WIRELESS SENSOR NETWORK FOR REAL-TIME MONITORING OF SOIL NPK LEVELS IN SUGARCANE PLANTATIONS - Tandin Wangmo; Jigme Dorji; Choden Tenzin (Yayasan Adra Karima Hubbi, 2025)
This study develops and tests a Wireless Sensor Network (WSN) system for real-time monitoring of soil nitrogen (N), phosphorus (P), and potassium (K) levels in sugarcane plantations. Traditional soil testing methods are time-consuming and costly, and they fail to provide continuous data on nutrient fluctuations, which limits effective decision-making in fertilization management. The study aims to evaluate the reliability and applicability of the WSN system in both agricultural field operations and as an educational tool for technology-enhanced learning. The research followed a design-and-testing methodology, developing sensor nodes with NPK soil sensors, microcontrollers, and wireless communication modules integrated into a centralized monitoring platform. Field testing took place in a sugarcane plantation, with sensor data continuously transmitted to a cloud-based dashboard for analysis. Results show that the WSN system accurately monitored spatial and temporal variations in soil NPK levels, providing stable data transmission with measurement accuracy comparable to laboratory soil analysis. Real-time visualization of nutrient status facilitated quicker interpretation and more responsive fertilization strategies. The study concludes that WSN-based soil monitoring is a practical, scalable solution for improving nutrient management in sugarcane plantations and offers potential as an educational tool to integrate digital sensing technologies into agricultural and vocational education.